Endovascular Treatment of Deep Hemorrhagic Brain Arteriovenous Malformations with Transvenous Onyx Embolization - Consoli, A.; Renieri, L.; Nappini, S.; Limbucci, N.; Mangiafico, S. (American Journal of Neuroradiology, 2013)
SUMMARY: Brain AVMs are a rare cause of cerebral hemorrhage and SAH, and their treatment is still debated. The aim of this study was to describe a novel endovascular approach with transvenous embolization of deep hemorrhagic brain AVMs. Five patients (3 females, 2 males; mean age, 33.2 years) underwent a transvenous embolization of a deep hemorrhagic brain AVM at our institution between February and April 2012. Clinical and angiographic data at the end of the procedure and after 6 months are reported. All the AVMs were completely obliterated, and no intra- or postprocedural complications occurred. The clinical outcome was unchanged or improved in all patients. Transvenous endovascular treatment may be considered in small, hemorrhagic, and deep AVMs with single deep drainage in those cases in which neurosurgical and radiosurgical treatment might not be indicated. ACAanterior cerebral arteryAchoAanterior choroidal arterybAVMsbrain AVMmRSmodified Rankin ScalePCAposterior cerebral artery